2020
DOI: 10.1038/s41440-020-00569-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of hyperkalemia during treatment with mineralocorticoid receptor blockers: findings from esaxerenone

Abstract: The nonsteroidal mineralocorticoid receptor (MR) blocker esaxerenone has demonstrated good antihypertensive activity in a variety of patients, including those with uncomplicated grade I–III hypertension, hypertension with moderate renal dysfunction, hypertension with type 2 diabetes mellitus with albuminuria, and hypertension associated with primary aldosteronism. Hyperkalemia has long been recognized as a potential side effect occurring during treatment with MR blockers, but there is a lack of understanding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 115 publications
(147 reference statements)
4
23
0
Order By: Relevance
“…Both doses of esaxerenone demonstrated efficacy in lowering blood pressure and were well tolerated. However, hyperkalaemia has long been recognized as a potential side effect that occurs during treatment with mineralocorticoid receptor blockers [ 5 ]. The approved dosing regimen of esaxerenone for hypertension is to initiate treatment at 2.5 mg once daily and titrate to a maximum of 5 mg once daily within 4 weeks when the effect is insufficient [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both doses of esaxerenone demonstrated efficacy in lowering blood pressure and were well tolerated. However, hyperkalaemia has long been recognized as a potential side effect that occurs during treatment with mineralocorticoid receptor blockers [ 5 ]. The approved dosing regimen of esaxerenone for hypertension is to initiate treatment at 2.5 mg once daily and titrate to a maximum of 5 mg once daily within 4 weeks when the effect is insufficient [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we were unable to follow-up the patients long-term, which seems to be one reason why the number of AEs was small. In previous studies regarding MRBs, however, K + elevation and eGFR decrease were reported to be most conspicuous within the first month [ 18 , 23 ]. We intended to investigate mainly the safety of the drug; thus, our results have a certain significance regarding safety.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalemia (K + >5.5 mEq/L) occurred in 11.8% [ 6 ]. Several phase III clinical trials of esaxerenone, which included patients with essential hypertension, hypertension with renal dysfunction, type 2 diabetes, or primary aldosteronism, but all without HF, showed that hyperkalemia occurred in 1.7% of esaxerenone-treated patients (including unpublished data) [ 12 , 16 18 ]. In the present study, no patient showed hyperkalemia, although K + was similarly elevated by 0.28±0.59 mEq/L in the first-MRB cohort in the short-term assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Esaxerenone was approved in Japan in 2019 for the treatment of essential hypertension (Duggan, 2019). Available data from phase III clinical trials suggests a similar incidence of hyperkalemia in patients treated with esaxerenone compared to eplerenone (Rakugi et al, 2021). Finerenone has very recently been approved by the United States Food and Drug Administration (FDA) for patients with chronic kidney disease associated with type 2 diabetes (FDA, 2021).…”
Section: Introductionmentioning
confidence: 99%